Conversion of CO2 and C2H6 to Propanoic Acid over a Au‐Exchanged MCM‐22 Zeolite. Issue 3 (20th December 2013) - Sangthong, Winyoo; Probst, Michael; Limtrakul, Jumras
Abstract Finding novel catalysts for the direct conversion of CO2 to fuels and chemicals is a primary goal in energy and environmental research. In this work, density functional theory (DFT) is used to study possible reaction mechanisms for the conversion of CO2 and C2H6 to propanoic acid over a gold‐exchanged MCM‐22 zeolite catalyst. The reaction begins with the activation of ethane to produce a gold ethyl hydride intermediate. Hydrogen transfers to the framework oxygen leads then to gold ethyl adsorbed on the Brønsted‐acid site. The energy barriers for these steps of ethane activation are 9.3 and 16.3 kcal mol−1, respectively. Two mechanisms of propanoic acid formation are investigated. In the first one, the insertion of CO2 into the AuH bond of the first intermediate yields gold carboxyl ethyl as subsequent intermediate. This is then converted to propanoic acid by forming the relevant CC bond. The activation energy of the rate‐determining step of this pathway is 48.2 kcal mol−1. In the second mechanism, CO2 interacts with gold ethyl adsorbed on the Brønsted‐acid site. Propanoic acid is formed via protonation of CO2 by the Brønsted acid and the simultaneous formation of a bond between CO2 and the ethyl group. The activation energy there is 44.2 kcal mol−1, favoring this second pathway at least at low temperatures. Gold‐exchanged MCM‐22 zeolite can therefore, at least in principle, be used as the catalyst for producing propanoic acid from CO2 and ethane.